Study On The Behavior Of Right-Turning Vehicles At Different Types Of Unsignalised Intersections In Malaysia - Vivian Lim, Wei Wen (Universiti Sains Malaysia, 2018)
Field study was carried out at different types of T-junctions which include a typical T-junction (Type A) and T-junctions (Type B and Type C) with short merging lane on the receiving approach. Type B junction has a short right-turn exit lane while Type C junction has a short through exit lane. From this study, the mean speed of vehicles making a right-turning maneuver from minor road as soon as they clear the conflict area were found to be 30.09 km/hr and 31.66 km/hr for Type B and Type C junctions respectively. Hence, the merging behavior of right-turning vehicles from minor road are similar for both junctions. There were 24.25% and 56.00% of major through movement vehicles reduced speed equal to or more than 5 km/hr when interacting with right-turning minor vehicles at Type B and Type C junctions respectively. Hence, the short merging lane in Type B junction reduces the conflict between right-turning vehicles from minor road and major road through movement vehicles in the far lane. The driver gap acceptance behavior was found to cease beyond gaps longer than 12s at Type A junction and 11s for both Type B and Type C junctions. The critical gap of right-turning minor vehicles for Type A, Type B and Type C junctions are 5.12s, 4.29s and 3.50s respectively. Therefore, Type C junction is more effective in reducing the critical gap of right-turning movement from minor road. The follow-up time at Type A junction is longer (3.30s) than Type B and Type C junction (both 2.97s) as drivers at Type A junction experienced more conflict. Type B junction was found to be better as it reduces the conflict of right-turning vehicles from minor road. Even though Type C junction reduces the critical gap of right-turning movement from minor road, but it affects the smooth movement of major through movement vehicles.